2018
DOI: 10.1021/acs.energyfuels.7b03363
|View full text |Cite
|
Sign up to set email alerts
|

Promotional Effect of Cu and Influence of Surface Ni–Cu Alloy for Enhanced H2 Yields from CH4 Decomposition over Cu-Modified Ni Supported on MCM-41 Catalyst

Abstract: Catalysts based on MCM-41 decorated with 35–70 nm diameter Ni particles were tested for the production of hydrogen by catalytic decomposition of methane (CDM). About 122 N m3 (molNi)−1 hydrogen yield was achieved over a catalyst comprised of optimized Ni loading of 50 wt % Ni/MCM-41. The H2 yield increased dramatically to 204 N m3 (molNi)−1, upon modification with 10 wt % Cu. The presence of Cu, in contact to Ni, appeared to reduce the sintering and coking of the active Ni sites, which enhanced the longevity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…In this regard, bimetallic catalysts based on the doping with low contents of noble (Ni-Cu, Ni-Pt, Ni-Pd), ferrous (Ni-Co, Ni-Fe) and refractory metals (Ni-Mo) were explored [8][9][10][11][12][13][14][15][16]. Among them, Cu doping involving the formation of the Ni (x) Cu (1-x) alloy stands out for enhancing the catalyst stability and activity at high temperature in addition to improving its reducibility and modifying the crystalline structure of the resulting carbon nanofilaments [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, bimetallic catalysts based on the doping with low contents of noble (Ni-Cu, Ni-Pt, Ni-Pd), ferrous (Ni-Co, Ni-Fe) and refractory metals (Ni-Mo) were explored [8][9][10][11][12][13][14][15][16]. Among them, Cu doping involving the formation of the Ni (x) Cu (1-x) alloy stands out for enhancing the catalyst stability and activity at high temperature in addition to improving its reducibility and modifying the crystalline structure of the resulting carbon nanofilaments [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Ni dispersion and sintering related challenges have also been addressed playing with the catalytic support [31][32][33] or the preparation method, which influence the formation of Nibased alloys when a dopant is involved in the catalyst preparation. Conventional supports for…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that Cu doping improved the reducibility of the Ni-based catalyst (Cu is easier to reduce than Ni) and enhanced its stability and activity in the CDM at high temperature [23][24][25][26][27][28][29][30][31][32][33][34]. The Ni-Cu alloy is formed over a wide composition range and at temperatures above 354 • C [35].…”
Section: Introductionmentioning
confidence: 99%